Chronic Achilles Tendon Ruptures: A Systematic Review. Issue 1 (January 2022) - Azam, Mohammad; Butler, James J.; Mercer, Nathaniel P.; Hurley, Eoghan; Shimozono, Yoshiharu; Kennedy, John G.
Category: Ankle; Trauma Introduction/Purpose: Chronic Achilles tendon ruptures (CATR) are an uncommon injury compared to acute ruptures. Currently, no evidence-based guidelines exist for treating CATR. The purpose of this systematic review was to present the outcomes of the current treatment options for CATR and to analyze the level of evidence (LOE) and quality of evidence (QoE) of the included studies. Methods: In July 2020, MEDLINE, EMBASE and Cochrane Library databases were systematically reviewed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The LOE and QOE of the included studies was evaluated using the Modified Coleman Methodology Score. Studies reporting outcomes following repair of CATR were included. Results: Thirty-one studies with 653 CATRs were included. Three studies were LOE III and 28 studies were LOE IV. Six studies reported dual technique procedures and 23 studies reported single technique procedures. Semitendinosus graft was the most frequently utilized single technique procedure amongst the included studies. Most studies reported good postoperative subjective outcomes, strength outcomes, and return to sports data at mid-term follow-up. In total, 14.6% of patients experienced postoperative complications. The most common complication was surgical wound complications (10.8%). Conclusion: This systematic review found that no evidence-based treatment guidelines exists for CATR. Surgical management of CATR produces good clinical outcomes at mid-term follow up, but a high complication rate (14.6%) was noted. Future studies of higher QOE and LOE with improved data reporting are warranted to determine the optimal treatment strategy for CATR.